Charge transport properties of MDMO PPV thin films cast in different solvents. Issue 20 (7th August 2015) - Raj Mohan, S.; Joshi, M. P.; Shalu, C.; Ghosh, C.; Mukharjee, C.; Kukreja, L. M.
ABSTRACT Charge transport properties in thin films of Poly(2‐methoxy‐5‐(3′, 7′‐dimethyloctyloxy)‐1, 4‐phenylenevinylene) (MDMO PPV) cast using either chloroform (CF), toluene (TOL), or chlorobenzene (CB) as solvent were investigated. Hole mobility (μ) in these thin films measured using time‐of‐flight transient photoconductivity showed an increasing trend with respect to the solvent used in the same order, that is, μCF (2.4 × 10−7 cm2/Vs) < μTOL (6.9 × 10−7 cm2/Vs) < μCB (2.3 × 10−6 cm2/Vs). Observed variations in mobilities were attributed to different morphologies of MDMO PPV chains in thin films cast using the aforesaid solvents. Nature of the interchain interactions and aggregate formation were obtained using photoluminescence (PL), Raman spectroscopy, and AFM studies. Ratio of PL peak intensities of 0–0 and 0–1 transitions, which is a direct measure of interchain interaction, was the highest in CB and lowest in CF. Variation in the relative intensities of out‐of‐plane wagging of vinylene group (∼963 cm−1 mode) in Raman spectra suggested different extent of coiling of polymer chains in these thin films. From these observations, it was elicited that aggregate size and interchain interactions are highest in CB and least in CF. AFM‐based topographic images of thin films further supported these variations in the size of aggregates. Variation in the aggregate sizes and interchain interactions explained the corresponding variation in the mobility. © 2015 Wiley Periodicals, Inc. J. Polym. Sci., Part B: Polym. Phys. 2015, 53, 1431–1439